Relationships between arsenic biotransformation genes, antibiotic resistance genes, and microbial function under different arsenic stresses during composting - Yongzhen Ding; Daoxian Li; Jiajia Li; Hui Lin; Zulin Zhang; Chein-Chi Chang; Suli Zhi (Environment International, 2024)
Although the arsenic contamination and antibiotic resistance genes (ARGs) during composting have been studied separately, there is limited information on their interactions, particularly, the relationship between arsenic biotransformation genes (ABGs) and ARGs. Therefore, the present study used different forms of arsenic stress (organic and inorganic arsenic at 10 and 50 mg/kg) in pig manure and straw co-composting, to evaluate the effects of arsenic stress on microbial community structures, metabolic function, ABGs, and ARGs. The results showed that arsenic stress had different effects on different parameters and promoted the microbial formation of humic acid and the biodegradation of fulvic acid. Inorganic arsenic showed more rapid effects on microbial community structure, visible within about 20 days, while the effects of organic arsenic were later (about 45 days) due to the necessity of transformation. Moreover, the addition of organic roxarsone and inorganic arsenic resulted in higher expression of ABGs and ARGs, respectively. Arsenic addition also caused increased expression of genes associated with replication and repair. A significant relationship was observed between ABG and ARG expression, for instance, genes involved in arsenic reduction and oxidation were influenced by genes involved in aminoglycoside and chloramphenicol resistance genes (p < 0.05). These complex interactions among microorganisms, functional genes, and external parameters contribute to the understanding of the mechanisms underlying cross-contamination.